Influencia del contexto en la estética de la narrativa de posguerra. - Gloria García-Blay, María; Micó Escrivá, Tomás Ernesto (Enunciación)
The aim of this paper is to review the context of the Spanish postwar period and to establish its relationship with the literary aesthetics of the different promotions of narrators. After an outline of the socioeconomic panorama, we analyzed the characteristics of the first postwar writers and the peculiarities of the existential novel based on the first works of Cela and Laforet. Next, we focus on the generation of the half century and its two movements, the social novel and neo realism. Finally, we reflecte the aesthetic changes of the decade from Tiempo de silencio.